2003
DOI: 10.1128/iai.71.1.354-364.2003
|View full text |Cite
|
Sign up to set email alerts
|

Differential Expression of Gamma Interferon mRNA Induced by Attenuated and VirulentMycobacterium tuberculosisin Guinea Pig Cells afterMycobacterium bovisBCG Vaccination

Abstract: To determine whether

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2003
2003
2009
2009

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 43 publications
1
27
0
Order By: Relevance
“…In either case, TNF-␣ induction in primary macrophages appears to be highly dependent on the experimental protocol and the origin of cells and bacterial strains under investigation. Our findings that TNF-␣ production positively correlates with the virulence of the mycobacterial strain employed demonstrates that, in guinea pigs, virulent mycobacteria may not effect a broad immunological "silence" implicated from previous studies in our laboratory (15,16,19). Instead, it is conceivable that M. tuberculosis H37Rv elevates host phagocyte TNF-␣ levels to facilitate its own survival by interfering with the production of IL-12 (20) and possibly increasing its availability to iron (10).…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…In either case, TNF-␣ induction in primary macrophages appears to be highly dependent on the experimental protocol and the origin of cells and bacterial strains under investigation. Our findings that TNF-␣ production positively correlates with the virulence of the mycobacterial strain employed demonstrates that, in guinea pigs, virulent mycobacteria may not effect a broad immunological "silence" implicated from previous studies in our laboratory (15,16,19). Instead, it is conceivable that M. tuberculosis H37Rv elevates host phagocyte TNF-␣ levels to facilitate its own survival by interfering with the production of IL-12 (20) and possibly increasing its availability to iron (10).…”
Section: Discussionsupporting
confidence: 54%
“…Previous work in this laboratory demonstrated that BCG vaccination in guinea pigs enhances both chemokine (RAN-TES and IL-8) and cytokine (IL-1-␤ and IFN-␥) mRNA responses from various cell cultures (i.e., alveolar macrophages, adherence-purified peritoneal exudate cells, and whole splenocytes [SPC]) (15,16,19). This vaccination effect was observed in response to different multiplicities of infection (MOIs) with various attenuated and virulent mycobacterial strains.…”
mentioning
confidence: 99%
“…The isolation of resident macrophages was based on established protocols (26,36). Euthanasia was carried out by intramuscular injection with 100 mg of sodium pentobarbital (Sleepaway; Fort Dodge Laboratories, Inc., Fort Dodge, Iowa)/kg of body weight.…”
Section: Methodsmentioning
confidence: 99%
“…Antibodies against guinea pig cytokines are not available for setting up guinea pig cytokine ELISA. So far, guinea pig IFN-γ, TNF-α, IL-1β, IL-2, IL-10, IL-12p40, GM-CSF, TGF-β and iNOS mRNA have been sequenced and their accession numbers are readily available [7,15,20], but RT-PCR has not been available for examining the expression of these mRNAs. Thus, our study is useful because our RT-PCR detects immunological changes in M. tuberculosis-infected guinea pig tissues at the mRNA level over time.…”
Section: (A) (B)mentioning
confidence: 99%
“…Bioassays for IFN-γ and TNF-α and northern blot analysis with limited cDNA probes have been used to examine the development of guinea pig TB [6,7,9,12]. Although real-time RT-PCR has been used recently to examine gene expression quantitatively [1,2,8,10], conventional RT-PCR is a more convenient method and uses cheaper reagents and devices [16-19, 22, 23].…”
Section: Introductionmentioning
confidence: 99%